UNSUR SUFISME DALAM JAMAâAH TABLIGH (Studi Kasus Jamaâah Tabligh di Kota Metro) - Hadi, Mukhtar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2014)
Submission of the people to God is limited by legal formal jurisprudence which is a set of procedures for worship. Though closeness to God can only be built with the submission, obedience and spiritual dialogue with God are needed. That is commonly practiced by Sufis and also perhaps by the Jamaâah Tabligh (JT). One of the teachings in the JT concept is to develop a simple lifestyle, full of modesty, moderation, also do not like to waste. Ushulul Dakwah has clearly illustrated that view by reducing four things namely: the time to eat and drink, sleep and rest period, a mosque and a time out to speak or perform activities in vain.Keywords: Sufisme, Jamaâah Tabligh